Membraniporina and Thalamoporellina (Bryozoa: Cheilostomatida) from the Konkan Coast, Maharashtra, India - Wayal, Dnyaneshwar V.; Sonar, Mohan A. (Zootaxa, 2026)
This paper reports ten species of Membraniporina and Thalamoporellina bryozoans collected along the Konkan coast of Maharashtra, India. Among these, Thalamoporella souleorum sp. nov. is described as new to science. Biflustra marcusi is recorded from India for the first time. Five species, Arbopercula angulata, Biflustra perambulata, Jellyella eburnea, Sinoflustra annae, and Thalamoporella hamata, are already known from the region. Three species (Arbocuspis sp., ?Einhornia sp., and Thalamoporella sp.) are left in open nomenclature owing to the poor preservation of the available material.